2014
DOI: 10.5897/ajar2013.7008
|View full text |Cite
|
Sign up to set email alerts
|

Bio fuel production and its implication on food security: Case study from Zambia

Abstract: The objective of this paper is to present a comprehensive review of the status quo of bio-fuels developments and the policy regimes including support measures driving the social, environmental and economic impacts of bio-fuels development. As it has been promoted by national policies markers, there is still no common consciences on its implication in achieving food security. The case study was based on a Meta evaluation carried out in Zambia; the key findings indicated that there is possible diversion of labou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…They concluded that there is possible diversion of labour and land to bio-fuel and competition of input that led to reduction of food production and high food prices (Teweldemedhin & Mwewa, 2013 , data (1979-2003) of the selected crops discovered that, "the production of biofuels would impact negatively on food production as fuel, food and industries compete for available crop stocks thereby …”
Section: Statement Of the Problemmentioning
confidence: 99%
“…They concluded that there is possible diversion of labour and land to bio-fuel and competition of input that led to reduction of food production and high food prices (Teweldemedhin & Mwewa, 2013 , data (1979-2003) of the selected crops discovered that, "the production of biofuels would impact negatively on food production as fuel, food and industries compete for available crop stocks thereby …”
Section: Statement Of the Problemmentioning
confidence: 99%
“…b. Agro-based residues are very essential in natural replenishing cycle of soil, and the continuous removal of crop residues will affect soil fertility, expose the soil to erosion, and poise a raising risk for food security. This may put pressure on global socioeconomic stability, especially to the less economically endowed regions of the world (Perlack et al 2005;Teweldemedhin and Mwewa 2014). c. Extracting biodiesel from oilseeds would create a shortfall for vegetable oil demands essentially needed for human consumption (Tariyal et al 2013).…”
Section: Agro-based Biomass Resourcesmentioning
confidence: 99%
“…This meant that farmers were either not going to find any markets for their farm produce or the market offer price may be very low. According to [49], low prices have usually been offered for Jatropha seed. In any business, markets and market information are two important components.…”
Section: Lack Of Compensatory Incentives Markets and Market Informationmentioning
confidence: 99%
“…The Zambian government has an Energy Regulation Act of 2008 and a Board to regulate production and utilization of biofuels [49]. However, the Act needs reviewing as it is outdated and there has also been no coordination and monitoring of Jatropha projects on the part of the government [52].…”
Section: Role Of Government: Unclear Policy On Jatropha and Bio Fuelsmentioning
confidence: 99%